Quantum Effect Dependent Modelling of Short Channel Junctionless Double Gate Stack(SC-JL-DG) MOSFET for High Frequency Analog Applications. (April 2023) - Udar, Prajvi; Goel, Anubha; Gupta, R.S.
Abstract: In this paper, the quantum effect has been induced on Junctionless (JL)-Double Gate metal-oxide-semiconductor field-effect transistors (JL-DGMOSFET) with gate oxide stack to study its effect on different device parameters like surface potential, threshold voltage, Id, Vg, gm, channel length etc. The study has been extended on Ion/Ioff change w.r.t. the variation in spacer width for varied channel thickness. In order to extend the efficacy of the results an analytical model has been formulated. The analytical model is developed by incorporating the Schrodinger equation in the conventional 2-D Poisson's equation, which has further been solved by applying the boundary conditions to obtain the final expression for potential and change in threshold voltage (Vth ). The device parameters are in accordance for both the simulated and analytical results. The simulation work has been supported by the ATLAS device simulation.